Formation conditions of natural gas fields in the lacustrine basin in eastern China: Insights into the first discovery within the Bohai Bay Basin - Xue, Yongan; Yang, Haifeng; Xu, Peng; Xiao, Shuguang (Frontiers in Earth Science, 2023)
The hydrocarbon source of Bohai Bay Basin is dominated by oil-prone kerogens of type II2-II1 within semi-deep and deep lacustrine facies. In the Neogene period, faults were well-developed via significant structural activity. The Bohai Sea is generally considered to have no geological basis for the formation of large natural gas fields. Through analogous analysis of domestic and international gas fields, the key geological factors that restrict formation in continental rift lacustrine basins were studied, including gas source, preservation conditions, and reservoirs. A natural gas enrichment and accumulation model within a petroliferous basin is presented. The model indicates that rapid subsidence and high-intensity gas generation within petroliferous sags during the late stages were main contributors to natural gas field formation. Archean metamorphic buried hill reservoirs and thick, overpressure mudstone with strong vertical sealing ability provided favorable storage space and preservation, respectively. Using the model, an integrated Archaean metamorphic buried hill condensate gas reservoir, Bozhong 19–6, was discovered in the Bohai Bay Basin. The natural gas reserves are about 450×109 m3, equivalent to oil production of 800 ×106 m3, and signify a breakthrough in natural gas exploration of continental rift lacustrine basins in China.